Novel mutations in genes encoding subcortical maternal complex proteins may cause human embryonic developmental arrest. Issue 6 (June 2018) - Wang, Xueqian; Song, Di; Mykytenko, Dmytro; Kuang, Yanping; Lv, Qifeng; Li, Bin; Chen, Biaobang; Mao, Xiaoyan; Xu, Yao; Zukin, Valery; Mazur, Pavlo; Mu, Jian; et al.
Abstract: Successful human reproduction initiates from normal gamete formation, fertilization and early embryonic development. Abnormalities in any of these steps will lead to infertility. Many infertile patients undergo several failures of IVF and intracytoplasmic sperm injection (ICSI) cycles, and embryonic developmental arrest is a common phenotype in cases of recurrent failure of IVF/ICSI attempts. However, the genetic basis for this phenotype is poorly understood. The subcortical maternal complex (SCMC) genes play important roles during embryonic development, and using whole-exome sequencing novel biallelic mutations in the SCMC genes TLE6, PADI6 and KHDC3L were identified in four patients with embryonic developmental arrest. A mutation in TLE6 was found in a patient with cleaved embryos that arrested on day 3 and failed to form blastocysts. Two patients with embryos that arrested at the cleavage stage had mutations in PADI6, and a mutation in KHDC3L was found in a patient with embryos arrested at the morula stage. No mutations were identified in these genes in an additional 80 patients. These findings provide further evidence for the important roles of TLE6, PADI6 and KHDC3L in embryonic development. This work lays the foundation for the genetic diagnosis of patients with recurrent IVF/ICSI failure.